O ensino de energia articulado às questões ambientais: limites e possibilidades de uma intervenção pedagógica no Ensino Médio - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present work aims to investigate the development of a pedagogical intervention, based on the Freirean thematic approach, and its contributions to the energy teaching-learning process and its articulated transformations to the environmental issues of the Pampa biome in the Physics discipline in a class. first year of high school. As a theoretical framework I assume the theoretical aspects of learning based on Vygotsky's historical cultural theory, the foundations of Education are founded on the principles of Paulo Freire's pedagogy. The teaching of Natural Sciences is based on a thematic approach that considers the context of the Pampa biome, in which a pedagogical intervention was developed based on the theme “Energy generation”. Environmental education is anchored in a critical-transformative and aesthetic perspective. Reflective writing portfolios produced by students and narratives constructed by the researcher-teacher compose the instruments of information production that were analyzed through the Narrative Analysis and Discursive Textual Analysis method, emerging three categories of analysis: a) Possible interpretations and pertinent questions about the conceptualization of energy and its transformations; b) Experimental class as a contribution to the learning of Energy and its transformations; and c) Environmental perceptions related to the study of energy. As an argument I defend the teaching of physics in a Freire's thematic approach to overcome the conceptual conception of curriculum, encouraging the insertion of experimental classes in the teaching-learning process and the articulation of environmental issues present in the Pampa biome, based on environmental education arguments. from a critical-transformative perspective. As an educational production of the teaching-learning process, a sequence of activities suggestive to the teaching work, which addresses the study of Energy related to the Pampa biome, is socialized.
Keywords: Geração de energia; Bioma Pampa; Ensino de ciências; Abordagem temática; Ensino Médio; Energy generation; Pampa biome; Science teaching; Thematic approach; High school; CNPQ::CIENCIAS SOCIAIS APLICADAS